Environmental and Dynamic Remote Monitoring of Historical Adobe Buildings: The Case Study of the Andahuaylillas Church in Cusco, Peru - Zonno G. (2019)
Constant survey of historical constructions is very important to ensure their conservation. In the case of ancient buildings, their use, the materials aging, vibrations, environmental effects (temperature, rain, snow) and seismic events are all possible causes of deterioration and damage. A continuous Structural Health Monitoring can provide useful information for automated condition evaluations of the health-state of historic buildings; however, it is known that the effects of environmental conditions such as the variation of temperature and humidity can make this assessment difficult. Therefore, continuous monitoring of environmental conditions and dynamic parameters is needed to develop suitable models to assess the current health-state. Additionally, historical structures could be located in a place where the harsh local conditions (viability, electricity, internet connection, etc.) or the distance from the inhabited centers can make monitoring activities challenging. This paper reports an innovative dynamic and environmental remote monitoring system implemented on the historical adobe church of San Pedro of Andahuaylillas, built in the sixteenth century, suitable example of Andean historical earthen constructions, strategically located on an Inca road system, 60km south of Cusco. Firstly, the monitoring methodology is discussed, and subsequently, the case study is presented. The data is recorded locally and is automatically sent to Lima (1200 km away from Cusco) where the dynamic data is automatically processed to identify the modal parameters of the church. Preliminary results of a 6-month monitoring campaign is finally shown.